Sums and products of indirect utility functions - Conniffe, Denis (Economic & Social Studies, 2002)
There are relatively few known demand systems that are theoretically satisfactory and practically implementable. This paper considers the possibility of deriving more complex demand systems from simpler known ones by considering sums and products of the component indirect utility functions, an approach that does not seem to have been exploited previously in the literature. While not all sums and products of valid utility functions need yield new valid utility functions, it is possible to usefully extend the range of available utility functions. Some of the demand systems that result are interesting and potentially useful: the simpler (in a parameter parsimony sense) for applied general equilibrium studies and for theoretical explication, while more complex systems have potential for the analysis of real world consumption data.
Paper presented at the Sixteenth Annual Conference of the Irish Economic Association
Keywords: Utility functions; Quantitative methods; Consumption; Demand